Time in Bed Is Associated with Decreased Physical Activity and Higher BMI in Women Seeking Weight Loss Treatment. (6th December 2012) - Hart, Chantelle N.; Fava, Joseph L.; Subak, Leslee L.; Stone, Katie; Vittinghoff, Eric; Demos, Kathryn E.; O'Brien, Erin; Cairns, Alyssa; Wing, Rena R.
Abstract : Short sleep duration is associated with obesity risk. Despite calls to incorporate strategies to enhance sleep within the context of behavioral weight loss (BWL) treatment, little is known regarding the association between sleep and body mass index (BMI) among individuals presenting for BWL. Moreover, most research has focused on eating pathways linking sleep and BMI and has not explored how sleep may impact engagement in physical activity. The purpose of the present study was to determine whether, in a sample of women seeking treatment for weight loss, there was an association between reported time in bed (TIB), higher BMI, lower physical activity, and less favorable dietary composition. Prior to randomization, 318 women completed measures of TIB, eating, and activity; weight and height were measured. Findings demonstrated that report of "6 hours or less" TIB/night was associated with higher BMI and lower reported physical activity compared to that of the referent (>7 to ≤8 hours/night). It was not associated with the number of reported calories consumed each day or with the percent of calories consumed from fat, carbohydrates, or protein. Better understanding of the role of sleep within the context of BWL treatment in women seems warranted.